PERAN TATA KELOLA PERUSAHAAN DALAM PENCEGAHAN BENTURAN KEPENTINGAN: STUDI LITERATUR: - - Nayaka Yafi Raihan; Ijtihad Jivat Rosidi; Afreza Abdillah Muhsin; Moh. Dimas Prameswara (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
Corporate governance plays a crucial role in enhancing transparency and accountability, particularly in preventing conflicts of interest that could harm a company's reputation. This study analyzes the relationship between corporate governance mechanisms, such as the proportion of independent commissioners, the frequency of audit committee meetings, institutional ownership, and environmental information disclosure, and company reputation. Using thematic analysis of scientific articles from 2019 to 2024, the findings reveal that effective governance mechanisms, such as intensive oversight by independent commissioners and proactive environmental disclosure, can improve public and investor perceptions. Good governance not only enhances financial performance but also strengthens corporate reputation through high levels of transparency and accountability.